Maternal Morbidity and Mortality Crisis in the United States: Strategies for Improvement from the White House and the Centers for Disease Control and Prevention. Issue 6 (November 2022) - Simpson, Kathleen Rice
Abstract : Recent recommendations from the White House and the Centers for Disease Control and Prevention for improvement in maternal health in the United States are covered. Despite multiple government reports identifying the problems and suggesting changes, maternal mortality is at an all time high in the United States and more than double the rates of peer countries.